2010
DOI: 10.1002/chem.200903220
|View full text |Cite
|
Sign up to set email alerts
|

Amminelithium Amidoborane Li(NH3)NH2BH3: A New Coordination Compound with Favorable Dehydrogenation Characteristics

Abstract: The monoammoniate of lithium amidoborane, Li(NH(3))NH(2)BH(3), was synthesized by treatment of LiNH(2)BH(3) with ammonia at room temperature. This compound exists in the amorphous state at room temperature, but at -20 degrees C crystallizes in the orthorhombic space group Pbca with lattice parameters of a = 9.711(4), b = 8.7027(5), c = 7.1999(1) A, and V = 608.51 A(3). The thermal decomposition behavior of this compound under argon and under ammonia was investigated. Through a series of experiments we have dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 52 publications
4
57
0
1
Order By: Relevance
“…CaAB was prepared according to literature procedures. [13] 15 N-labeled CaAB·2 NH 3 was prepared by reacting Ca( 15 NH 2 ) 2 with unlabeled AB (molar ratio of 1:2) . All materials were handled inside a glove-box filled with purified argon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CaAB was prepared according to literature procedures. [13] 15 N-labeled CaAB·2 NH 3 was prepared by reacting Ca( 15 NH 2 ) 2 with unlabeled AB (molar ratio of 1:2) . All materials were handled inside a glove-box filled with purified argon.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Kim and co-workers suggested that the metal cation "relays" the hydride, and the barrier for transfer was found to correlate with the ionic character of the metal-hydride interaction. [9] More recently, a new subfamily of metal amidoboranes, which are known as metal amidoborane ammoniates, was prepared by reacting AB with Ca(NH 2 ) 2 , LiNH 2 , or MgNH, yielding Ca(NH 2 BH 3 ) 2 ·2 NH 3 (CaAB·2 NH 3 ), [11] Li(NH 2 BH 3 ) 2 ·NH 3 (LiAB·NH 3 ), [12,13] and Mg(NH 2 BH 3 ) 2 ·NH 3 (MgAB·NH 3 ). [14] The hydrogen contents of these compounds are ca.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of B-N amidoborane ammoniates, have previously been synthesized by reacting MAB and NH3, including LiNH2BH3·NH3 [16], Mg(NH2BH3)2·3NH3 [17], and Ca(NH2BH3)2·NH3 [18]. However, to the best of our knowledge, there has been no prior report of the synthesis of an aluminum analog.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 These ammoniates demonstrated significantly improved dehydrogenation properties owing to the active participation of NH 3 in the dehydrogenation process. Despite the salient role of NH 3 in the ammoniate complexes, contamination of H 2 by a small amount of NH 3 is unavoidable.…”
Section: ■ Introductionmentioning
confidence: 99%